Praktik Tata Kelola dalam Perspektif Nilai Budaya Lokal pada Lembaga Perkreditan Desa (LPD) - Ketut Sonya Adnyani (Master in Accounting Program, 2017)
Village Credit Institution (Lembaga Perkreditan Desa or LPD) is a community financial institution located in Bali Province. The purpose of LPD is to help customary village in implementing its cultural functions. LPD has been proven to improve the economic, social and cultural conditions of the society. Currently, the existence of LPD is strengthened by the issuance of Law of Micro Finance Institution No. 1 of 2013. Based on that law, LPD is regulated based on customary law of each village. In fact, not all LPDs are able to develop sustainably. One of the factors that causing the problem is the lack of awareness to realize good governance practices in conflict prevention between management and village communities as the LPD owners. Good governance practices should fulfil the principles of transparency, accountability, responsibility, independence and fairness. Therefore, it is important to review the practice of governance seen from the perspective of local cultural values. The local cultural value used in this research is catur purusa artha, consisting of dharma, artha, kama and moksa. This research was conducted at LPD Pecatu. Qualitative data are collected through interviews with 5 informant in corporate level, observations and documentations and analyzed by coding and content analysis.The results showed that LPD Pecatu have done a good governance practices. The value of local culture is closely related to governance practices which can be seen through the behaviors and policies that are made by leaders in LPD. However, there are some things that need to be improved such as performance evaluation and employee rotation.